A closer look at the role of Zn in the microstructure and corrosion of an Al-Cu-Li alloy. (December 2018) - Liu, D.Y.; Li, J.F.; Ma, Y.L.; Gupta, R.K.; Birbilis, N.; Zhang, R.
Highlights: The IGC resistance difference of the Al-Cu-Li alloys with different Zn-additions is investigated. Three types of phase at GBs were confirmed. Zn exists in the coarsen phase at the GBs. The quantity and space of the coarse phases at the GBs are attached to Zn-addition. The potential difference between the conversed coarse phase and adjacent zone decreases contributing to the increasing corrosion resistance. Abstract: The influence of various amounts of Zn addition on the microstructure and associated intergranular corrosion of Al-2.8Cu-1.7Li-0.4Mg-0.3Mn-0.12Zr alloys was studied using transmission electron microscopy coupled with energy-dispersive X-ray spectroscopy, and corrosion and electrochemical techniques. The added Zn was incorporated into the precipitates at the grain boundaries (GBs). Three types of phases at the GBs were confirmed. The quantity and space of the coarse phases at the GBs were related to Zn addition. The Zn addition decreased the potential difference between the conversed coarse phase (containing Zn) and the adjacent matrix, which improved the intergranular corrosion resistance.